Psychological Well-Being in Married Individuals: Examining Role of Conscientiousness Personality Trait - Meta Damariyanti; Sofia Retnowati; Ira Puspitawati; Wahyu Rahardjo (Psympathic : Jurnal Ilmiah Psikologi, 2022)
This study investigates the influence of conscientiousness personality trait on psychological well-being of married individuals facing complex life issues. The attainment of psychological well-being is essential for individuals to cope and thrive during challenging times. Conscientiousness trait is known to promote commitment and a drive to achieve life goals, which can positively affect psychological well-being of married individuals. The study adopts a quantitative approach with 144 married participants (92 females and 52 males) aged 21-63 years. The primary analytical techniques use simple regression and correlation as additional analyses to examine the relationship between conscientiousness and psychological well-being, as well as the dimensions of both variables. The results show that conscientiousness has an influence on psychological well-being, and correlates with all aspects of the variable.